1996
DOI: 10.1111/j.1399-6576.1996.tb05552.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre‐ vs postoperative tonsillar infiltration with local anesthetics on postoperative pain after tonsillectomy

Abstract: Background: Since pre‐incisional peritonsillar infiltrations of local anesthetic solutions have been suggested to reduce postoperative pain after tonsillectomy, we compared the efficacy of either pre‐ or postoperative local anesthetic infiltration upon post‐tonsillectomy pain.Methods: After the induction of general anesthesia, 68 consecutive healthy patients, ranging in age from 8 to 65 years, were randomly allocated to either receive peritonsillar infiltration with 0.25% bupivacaine (group 1) or normal saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 24 publications
4
58
0
4
Order By: Relevance
“…13 There are numerous studies in which a local anesthetic has been applied to the tonsillar fossae in tonsillectomy. The local anesthetic is usually applied by infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…13 There are numerous studies in which a local anesthetic has been applied to the tonsillar fossae in tonsillectomy. The local anesthetic is usually applied by infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that there was not a significant difference between the bupivacaine pre-and post-incisional groups in pain reduction, but there was a significant difference in these groups compared to the saline groups. This study did address the use of other analgesics (acetaminophen) when assessing the VAS score, but the researchers did not note doses or frequency of those analgesics, as they were looking at the pre versus post-incisional infiltration and if differences in post-operative pain was more effective in the pre-versus the post-incisional groups [30]. This study suggests that in tonsillectomy either pre-or-post-incisional infiltration of bupivacaine may produce a reduction in post-surgical pain when compared to the saline (control) group.…”
Section: Resultsmentioning
confidence: 99%
“…In comparing pre and postoperative local anesthetics infiltration literature results are conflicting. A study testing pre and postoperative bupivacaine infiltration in tonsillectomies has not found differences in analgesic control 22 . Similarly, a different study has not found pain intensity differences after mastectomy with pre or postoperative incision infiltration 23 .…”
Section: Discussionmentioning
confidence: 99%